Multiple Sclerosis Relapsing Remitting Progressive Type - Nora Fitri; Basjiruddin Ahmad; Yuliarni Syafrita (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Multiple sclerosis (MS) is the most common neurologic demyelinating disease in high-income countries. The causes of MS is multifactorial involve genetics and the environment in which immune cell infiltration occurs across the blood-brain barrier, causing inflammation, demyelination, gliosis, and neuroaxonal degeneration in the substantia grisea in the central nervous system. A 23-year-old female patient was treated with four limbs weakened since 2 weeks ago accompanied by blurred vision, pain, cramps and stiffness in the back muscles and legs. The patient has experienced the same complaint before. Clinical findings reveal lhermitte sign, atrophy papillae, and tetraparese. On thoracic vertebral MRI examination without contrast and brain MRI with contrast obtained multiple sclerosis lesions. Patients receive steroid and antidepressant therapy. MS needs to be studied further because this number of cases began to emerge.